Pelvic Floor Rehabilitation in the Treatment of Fecal Incontinence - Scott, Kelly M. (Clinics in Colon and Rectal Surgery, 2014)
Fecal incontinence (FI) is a prevalent problem that can drastically affect quality of life. Pelvic floor rehabilitation is an important first-line treatment for patients with FI, and many published case reports and a small number of randomized controlled trials (RCTs) provide limited evidence for its efficacy. Pelvic floor rehabilitation approaches to the treatment of FI include pelvic floor muscle training, biofeedback, and volumetric training with rectal balloon catheters. Various forms of external electrical stimulation have also been described and may be of added benefit. Behavioral bowel retraining is an important part of a good rehabilitative approach as well. Pelvic floor rehabilitation treatment for FI is thought to be effective and safe, with reported success rates in a majority of studies at 50 to 80%. Many more high-quality RCTs are needed to define optimal treatment protocols.
Keywords: fecal incontinence; pelvic floor muscle training; biofeedback